Who becomes a tenured professor, and why? Panel data evidence from German sociology, 1980-2013 - Mark Lutter; Martin Schröder (Max Planck Institute for the Study of Societies, 2014)
Prior studies that try to explain who gets tenure and why remain inconclusive, especially on whether non-meritocratic factors influence who becomes a professor. On the basis of career and publication data of virtually all sociologists working in German sociology departments, we test how meritocratic factors (academic productivity) as well as non-meritocratic factors (ascription, symbolic, and social capital) influence the chances of getting a permanent professorship in sociology. Our findings show that getting tenure in sociology largely depends on scholarly output, as previous studies have shown. Improving on existing studies, however, we show specifically that each refereed journal article and each monograph increases a sociologist's chance for tenure by 10 to 15 percent, while other publications affect one's likelihood for tenure only marginally and in some cases even negatively. Regarding non-meritocratic factors, we show that network size and individual reputation matter, while international experience and the reputation of one's university do not directly affect the likelihood of tenure. Women need on average 23 to 44 percent fewer publications than men to get their first permanent position as university professor. Thus, all else being equal, they are about 1.4 times more likely to get tenure than men. The article contributes to a better understanding of the role of meritocratic and non-meritocratic factors in achieving scarce and highly competitive job positions. – – Bei der Frage, wer eine Professur bekommt, sind sich bisherige Studien insbesondere über den Einfluss nichtmeritokratischer Faktoren unschlüssig. Auf Basis von Lebenslauf- und Publikationsdaten fast aller an soziologischen Instituten in Deutschland beschäftigten Sozialwissenschaftlerinnen und Sozialwissenschaftlern testen wir, wie meritokratische (wissenschaftliche Produktivität) und nichtmeritokratische Faktoren (Askription, symbolisches und soziales Kapital) die Chance beeinflussen, auf eine Soziologieprofessur berufen zu werden. Es zeigt sich, dass eine Berufung vor allem von der Anzahl wissenschaftlicher Publikationen abhängt. Mit jedem referierten Zeitschriftenaufsatz und jeder Buchpublikation steigt die Chance auf eine Berufung um 10 bis 15 Prozent an, während andere Publikationsarten sie nur moderat oder sogar negativ beeinflussen. Unter den nicht-meritokratischen Faktoren zeigen sich insbesondere Netzwerkfaktoren wie auch individuelle Reputation als relevant. Internationale Erfahrung sowie das Prestige der Herkunftsinstitution weisen keine direkten Effekte auf. Frauen, so das weitere Ergebnis der Untersuchung, benötigen im Schnitt 23 bis 44 Prozent weniger Publikationen als Männer, um einen Erstruf zu erhalten. Unter sonst gleichen Faktoren liegt ihre Chance auf eine Professur um das 1,4-fache höher als die ihrer männlichen Kollegen. Insgesamt leistet die Studie einen Beitrag zur Beantwortung der Frage, wie und wie stark meritokratische und nichtmeritokratische Faktoren die Chancen auf sehr knappe, zugleich hoch kompetitive Berufspositionen beeinflussen.
Keywords: 300